Tracing Bong Lie Phin’s ceramic artistry in Singkawang: unveiling cultural heritage and technological advancements (1989-2020) - Iwan Pranoto; M. Agus Burhan; Muhamad Romadoni (Pascasarjana Institut Seni Indonesia Surakarta, 2023)
Ceramics by artist Bong Lie Phin has a historical record in the world of art by bringing social change to form a new culture through ceramic works. Another thing about ceramic development technology. This research is important in order to provide renewal through ceramic works. As for the research question, namely, how are inductive empiricism, reconstruction, and humanism related to ideas, society, and technology? This research process used qualitative methods with historical, social, and technological approaches and data collection techniques through interviews, literature studies, notes, and documentation documents. In the process of collecting data, researchers will gather information from artists and other supporting data. The data needed is in accordance with the research questions and then tested by involving experts and artists. There are several findings that the artist Bong Lie Phin created works from 1989 to 2020 with the concept of Chinese mythology and interpreted Chinese cultural symbols. This is also supported by the exploration of materials and technologies that develop in making ceramics, but without reducing the value and meaning, it was found that there were financial support factors carried out by the management of these ceramic artists in influencing understanding. Work so that the presence of work continues. Occurs, the work is considered capable of providing transformation of spiritual values; another discussion is the community's contribution in providing understanding in the creation of ceramic art so that the process of reconstruction in the work occurs continuously.